PENERAPAN SISTEM HAZARD ANALYSIS CRITICAL CONTROL POINT (HACCP) PADA PROSES PEMBUATAN KERIPIK TEMPE - Yuniarti, Rahmi; Azlia, Wifqi; Sari, Ratih Ardia (Universitas Muhammadiyah Surakarta, 2015)
Malang is one of the industrial centers of tempe chips. To maintain the quality and food safety, analysis is required to identify the hazards during the production process. This study was conducted to identify the hazards during the production process of tempe chips and provide recommendations for developing a HACCP system. The phases of production process of tempe chips are started from slice the tempe, move it to the kitchen, coat it with flour dough, fry it in the pan, drain it, package it, and then storage it. There are 3 types of potential hazards in terms of biological, physical, and chemical during the production process. With the CCP identification, there are three processes that have Critical Control Point. There are the process of slicing tempe, immersion ofÂ tempe into the flour mixture and draining. Recommendations for the development of HACCP systems include recommendations related to employee hygiene, supporting equipment, 5-S analysis, and the production layout.Â